Multi-Objective Optimization Design of the Small Flow Rate Emitter Structure Based on the NSGA-II Genetic Algorithm - Zongze Yang; Yan Mo; Chunlong Zhao; Huaiyu Liu; Yanqun Zhang; Juan Xiao; Shihong Gong; Yanan Bi (Agriculture)
Reducing the flow rate (q) of the emitter can increase the dripline laying length and reduce the engineering investment of the drip irrigation system; however, reducing q increases the risk of emitter clogging. In this study, based on the OPFN method (Optimal Latin Hypercube Experimental Design–Parametric Modeling of Emitter–Fluid Dynamics Simulation–NSGA-II Genetic Algorithm Optimization), we selected the structural parameters of channel tooth height (E), angle (A), pitch of teeth (B), and flow channel depth (D) to construct 128 emitters. Through simulation, we obtained q, the flow index (x), and the structural resistance coefficient (Cs) under the pressure (H) ranging from 0.02 to 0.15 MPa. The results showed that the rated flow rate (q0.1) and x values of 128 emitters range from 0.50 to 0.85 L/h and 0.461 to 0.480, respectively. Since Cs is negatively correlated with x, to obtain the combination of the flow channel structural parameters with the optimal hydraulic performance (x = min f(E, A, B, D)) and the optimal anti-clogging performance (Cs = min g(E, A, B, D)), the flow channel structural parameters are optimized by using the NSGA-II genetic algorithm to obtain the Pareto frontier solution. The optimal combinations of channel structural parameters corresponding to the q0.1 values of 0.62, 0.71, and 0.82 L/h with x of 0.470, 0.466, and 0.463 are obtained using the weighting method. Cs values are 0.131, 0.446, and 0.619, respectively. The limit laying length of the configured emitter is 150–180 m. According to the flow field cloud diagram before and after optimization, it can be found that increasing the high-velocity area and high-turbulent-kinetic-energy area in the main stream and decreasing the low-velocity area and low-turbulent-kinetic-energy area in the tooth base and downstream face can help reduce x and Cs, and thus improve the hydraulic performance and anti-clogging performance of the small flow rate emitter.